The Impact of Internet Marketing on the Development of Social and Economic Interaction Between Governments (Case Study: Internet Marketing by Iranian Private Companies in Iraq and Its Effect on Enhancing Social and Economic Interaction Between the Governments of Iran and Iraq) - Tofiq Ahmed, Basoz; Hajipour, Bahman; Azizi, Shahriar (Business, Marketing, and Finance Open, 2026)
In recent decades, internet marketing has emerged as one of the most important tools for the development of international business. The present study examines the role of internet marketing by Iranian private companies in the Iraqi market and its impact on fostering economic, social, and cultural interactions between the two countries. This qualitative study was conducted through 18 semi-structured interviews with managers and marketing experts from private companies active in the Iraqi market. Data were analyzed using a thematic analysis approach and processed with MAXQDA software, resulting in the extraction of four main themes: strengthening inter-organizational trust and social capital, digital marketing as a tool of economic soft power, facilitating intercultural interactions, and creating informal channels of economic diplomacy. The findings indicated that internet marketing has not only enhanced export performance and expanded access to new markets but has also played a key role in strengthening trust between companies and customers, expanding cultural and social connections, and facilitating economic diplomacy. Furthermore, causal factors such as the growth of digital technologies, competitive pressures, and economic constraints; contextual conditions including inadequate infrastructure and cultural differences; and mediating factors such as digital skills and government regulations have influenced the success of this process. By offering strategies such as content localization, continuous engagement with customers, and leveraging shared cultural symbols, the study demonstrates how Iranian companies have been able to manage challenges and capitalize on digital marketing opportunities in the Iraqi market. The results of this research hold particular significance for policymakers and marketing managers and can serve as a practical guide for developing cross-border digital marketing strategies.